Oppia nitens C.L. Koch, 1836 (Acari: Oribatida): Current Status of Its Bionomics and Relevance as a Model Invertebrate in Soil Ecotoxicology. (22nd November 2019) - Fajana, Hamzat O.; Gainer, Amy; Jegede, Olukayode O.; Awuah, Kobby F.; Princz, Juliska I.; Owojori, Olugbenga J.; Siciliano, Steven D.
Abstract: The oribatid soil mite Oppia nitens C.L. Koch, 1836, is a model microarthropod in soil ecotoxicity testing. This species has a significant role in supporting soil functions and as a suitable indicator of soil contamination. Despite its significance to the environment and to ecotoxicology, however, very little is known of its biology, ecology, and suborganismal responses to contaminants in the soil. In the present review, we present detailed and critical insights into the biology and ecology of O. nitens in relation to traits that are crucial to its adaptive responses to contaminants in soil. We used a species sensitivity distribution model to rank the species sensitivity to heavy metals (cadmium and zinc) and neonicotinoids (imidacloprid and thiacloprid) compared with other standardized soil invertebrates. Although the International Organization for Standardization and Environment and Climate Change Canada are currently standardizing a protocol for the use of O . nitens in soil toxicity testing, we believe that O . nitens is limited as a model soil invertebrate until the molecular pathways associated with its response to contaminants are better understood. These pathways can only be elucidated with information from the mites' genome or transcriptome, which is currently lacking. Despite this limitation, we propose a possible molecular pathway to metal tolerance and a putative adverse outcome pathway to heavy metal toxicity in O . nitens . Environ Toxicol Chem 2019;38:2593–2613. © 2019 SETAC